Views of the Sociology of Religion Regarding the LGBT Phenomenon: When Love is Used as a Reason and Religion is Neglected - Fatimah, Widia Priandini; Komariah, Siti; Wulandari, Puspita (Indev: Literasi Media Dakwah dan Pengembangan Masyarakat, 2024)
Love is an abstract thing that often cannot be described through a theory or string of words. Because basically love is a feeling of affection that is felt by the heart and difficult to digest by logic. When love has spoken often norms and religions are neglected. And one of them is the LGBT social phenomenon based on reasons of love. The purpose of this article is to find out whether in a relationship can only be based on love and religion will be neglected. The research method used is the study of literature using systematic review by collecting and reviewing from several relevant reference sources related to the sociological view of religion in LGBT relations based on reasons of love. Collection of reference sources is done by searching online databases through Google Schoolar as a data search. Based on the study of literature from various sources, the results of the study showed that LGBT is a deviant behavior and cannot be justified even under the pretext of love. Therefore, there needs to be a broader understanding and socialization related to LGBT in order to understand that LGBT is a behavior that not only deviates in norms and religions, but is constitutionally prohibited and has been declared as deviant behavior.